2006
DOI: 10.1038/oby.2006.172
|View full text |Cite
|
Sign up to set email alerts
|

The Promoter Region of the Adiponectin Gene Is a Determinant in Modulating Insulin Sensitivity in Childhood Obesity

Abstract: We investigated the association of the Ϫ11,391GϾA, Ϫ11,377GϾC, ϩ45TϾG, and ϩ276GϾT adiponectin single-nucleotide polymorphisms (SNPs) and expected haplotypes with the insulin resistance (IR) state in overweight/ obese children; by using the haplotype background analysis, we also assessed the effect of each SNP independently. GG genotype at the Ϫ11,391 locus was associated with higher fasting insulin levels and homeostasis model assessment-IR index and lower adiponectin levels compared with GA ϩ AA genotypes (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
53
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 21 publications
(40 reference statements)
12
53
1
4
Order By: Relevance
“…In contrast, some other studies demonstrated that the common -11377C allele was strongly associated with obesity and MetS parameters (17,52). Our findings are also consistent with previous reports in different populations and different age groups (53,54,55) stating that ADIPOQ gene may play an important role in MetS. Results of these reports pointed that regional differences in body fat affected the risk of metabolic abnormalities, and also ADIPOQ gene variants were suggested as modulators of visceral fat accumulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, some other studies demonstrated that the common -11377C allele was strongly associated with obesity and MetS parameters (17,52). Our findings are also consistent with previous reports in different populations and different age groups (53,54,55) stating that ADIPOQ gene may play an important role in MetS. Results of these reports pointed that regional differences in body fat affected the risk of metabolic abnormalities, and also ADIPOQ gene variants were suggested as modulators of visceral fat accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…Identification of genes controlling adiponectin levels may aid our understanding of how genes influence MetS and possibly obesity (56). Many study results were published on associations of ADIPOQ SNPs (27,36,57) as well as haplotypes with plasma adiponectin concentrations (22,54), but the data are controversial. Association between serum adiponectin level and ADIPOQ variants represents one of the several mechanisms that can be considered as a link between ADIPOQ and MetS.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies 9, 18,19 we found standardized linkage disequilibrium between À11391 and À11377 SNPs. In this context, haplotype combinations could clarify associations involving these correlated markers.…”
Section: Discussionsupporting
confidence: 58%
“…Despite the low number of subjects measured for adiponectin levels, our results were in close agreement with other studies. [8][9][10]18,19 It has been previously described in different obese and nonobese populations that plasma concentrations of adiponectin are significantly higher in À11391A allele carriers, while À11377C4G ADIPOQ polymorphism induced lower adiponectin levels. Furthermore, transcriptional activity of the ADIPOQ promoter, measured with a luciferase assay, demonstrated that the À11391G4A polymorphism had a 2.5-fold increase in transcriptional activity, which was in accordance with higher adiponectin levels observed in À11391A carriers.…”
Section: Discussionmentioning
confidence: 97%
“…In an earlier study of SNP at the ADIPOQ locus -11391 G/A, -10066 G/A, -7734 A/C and + 276 G/T in this laboratory, we found -10066G, -11391A, -7734A and + 276T were significantly associated with higher serum adiponectin concentration in two large cohorts (104) . Association of elevated adiponectin with the -11391 A-allele has been reported widely (102,(105)(106)(107)(108) , although one group found lower adiponectin in G-allele carriers (109) . Associations between + 276G and lower adiponectin concentrations have also been reported in Spanish (110) , European (111) , Korean (112) and Japanese (113) subjects.…”
Section: Adipoq Gene Polymorphismsmentioning
confidence: 99%